Synchronous failure diagnosis of discrete-event systems - Cabral, Felipe Gomes de Oliveira (2017)
In general, systems are formed by the composition of several modules, local components or subsystems, and may exhibit a large number of states. The growth of the global system model with the number of system components leads to high computational costs for failure diagnosis techniques based on the global model. In this work, a new approach for the failure diagnosis of discrete event systems is introduced. The method is based on the computation of a Petri net diagnoser, called synchronized Petri net diagnoser (SPND), that is constructed from the nonfailure behavior of the modules of the system. We also introduce the de nition of synchronous diagnosability of the language of a system with respect to the languages of its modules, and present an algorithm to verify this property. We also propose a decentralized synchronized Petri net diagnosis scheme for discrete-event systems modeled as automata. In order to do so, we de ne the notion of synchronous codiagnosability and propose an algorithm to verify this property. The synchronized diagnosis can be re ned using the global nonfailure model of the system, leading to the notion of conditional synchronous diagnosability. An algorithm for the veri cation of conditional synchronous diagnosability based on the veri cation of synchronous diagnosability is proposed. We also discuss the relation among conditional synchronous diagnosability, synchronous codiagnosability, synchronous diagnosability and diagnosability of discrete-event systems. Algorithms for the computation of the maximum delay bound for all diagnosis schemes presented in this work are proposed. An example and a practical implementation of the diagnosis methods are presented and used throughout this work in order to illustrate and validate the methods.